2020
DOI: 10.3892/mmr.2020.11097
|View full text |Cite
|
Sign up to set email alerts
|

A HGF‑derived peptide suppresses EMT in human lens epithelial cells via the TGF‑β/Smad and Akt/mTOR signaling pathways

Abstract: Posterior capsule opacification (PCO) as a result of proliferation and fibrogenesis of lens epithelial cells (LECs) is the most frequent long-term complication of modern cataract surgery. LECs may undergo epithelial-mesenchymal transition (EMT) that resembles the morphological and molecular characteristics of PCO. A pre-identified novel, hepatocyte growth factor (HGF)-derived peptide H-RN, was reported to exhibit anti-angiogenic activity and anti-inflammatory effects in ocular cells both in vitro and in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…This equilibrium is crucial because net plasminogen activity contributes to the degradation of excessive fibrin clots, preventing fibrin accumulation and further adhesion development. Previous reports have demonstrated that human recombinant HGF promotes the tPA expression while downregulating PAI-1 expression, leading to a higher net plasminogen activity. , Importantly, HGF has been found to hamper the Smad2/3 pathway by inducing the inhibitory messenger Smad7, suggesting that HGF is effective in regulating multiple Smad2/3-mediated events. , In this study, the HGF DNA aptamer effectively restored the elevated PAI-1 expression induced by TGF-β to the basal level, whereas it induced tPA expression above baseline compared to the control group. These results confirm the efficacy of the HGF DNA aptamer in promoting fibrinolytic activity, and the increase in tPA expression was consistent with the downregulation of PAI-1.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This equilibrium is crucial because net plasminogen activity contributes to the degradation of excessive fibrin clots, preventing fibrin accumulation and further adhesion development. Previous reports have demonstrated that human recombinant HGF promotes the tPA expression while downregulating PAI-1 expression, leading to a higher net plasminogen activity. , Importantly, HGF has been found to hamper the Smad2/3 pathway by inducing the inhibitory messenger Smad7, suggesting that HGF is effective in regulating multiple Smad2/3-mediated events. , In this study, the HGF DNA aptamer effectively restored the elevated PAI-1 expression induced by TGF-β to the basal level, whereas it induced tPA expression above baseline compared to the control group. These results confirm the efficacy of the HGF DNA aptamer in promoting fibrinolytic activity, and the increase in tPA expression was consistent with the downregulation of PAI-1.…”
Section: Discussionsupporting
confidence: 52%
“…56,62 Importantly, HGF has been found to hamper the Smad2/3 pathway by inducing the inhibitory messenger Smad7, suggesting that HGF is effective in regulating multiple Smad2/3-mediated events. 55,63 In this study, the HGF DNA aptamer effectively restored the elevated PAI-1 expression induced by TGF-β to the basal level, whereas it induced tPA expression above baseline compared to the control group. These results confirm the efficacy of the HGF DNA aptamer in promoting fibrinolytic activity, and the increase in tPA expression was consistent with the downregulation of PAI-1.…”
Section: ■ Discussionmentioning
confidence: 58%
“…Hepatocyte growth factor splice variant NK1 (HGF/NK1) and bone morphogenetic protein 7 (BMP7) are two growth factors with demonstrated potent anti-fibrotic activities [ 22 , 23 ]. Huang and colleagues [ 15 ] employed H-RN peptide, derived from the kringle 1 domain present in HGF/NK1, to show in vitro inhibition of TGF-β2/Smad2/3-dependent induction of epithelial-mesenchymal transition (EMT) in lens epithelial cells, preventing their acquisition of myofibroblastic markers. H-RN also prevented TGF-β2/Smad-independent activation of Akt, mTOR, and p70S6K.…”
Section: Direct Targeting Of Myofibroblast Pathways With Peptidesmentioning
confidence: 99%
“…We found the TGF-β signalling pathway to be one of the primary pathways for NPM1 enrichment. This signalling system has been shown to have a function in the creation and maintenance of the eye lens (47,48). TGF-β family is critical for regulating cell differentiation and other physiological processes and its dysregulation is linked to developmental defects, illness, cancer, and fibrosis (49,50).…”
Section: Discussionmentioning
confidence: 99%